FREQUENCY OF TP53 GENE MUTATION IN PATIENTS WITH CHRONIC LYMPHOCYTIC LEUKAEMIA - Qadir, Hira; Nasir, Nadia; Qadir, Nida; Adil, Salman Naseem; Tanzeem, Hammad; Qadir, Areesha (Journal of Ayub Medical College Abbottabad, 2020)
Background: Chronic lymphocytic leukaemia (CLL), an indolent but malignant lymphoproliferative disorder, is characterized by unregulated and uninhibited growth of mature monoclonal lymphocytes, with deletion of 17p containing TP53 gene being the most important prognostic factor. TP53 mutations, reported in 10% of CLL cases, seem to have a direct correlation to a more advanced stage and aggressive transformation of CLL. Methods:This was a retrospective cross-sectional descriptive study limited to a period from 1st June 2013 to 30th June 2016, conducted at Section of haematology, Department of Pathology and Laboratory Medicine, Aga Khan University Hospital, Karachi. One thirty-nine cases of CLL received for TP53 mutation analysis at the Aga Khan University hospital clinical Laboratory were included in the study. Five ml of whole blood or one ml of bone marrow aspirate sample in EDTA tube was collected for the detection of TP53 mutation by the FISH technique. Statistical package for social sciences 21 was used for data entry and analysis. Results: Of the 139 chronic lymphocytic leukaemia patients, 43 (31%) were females and 96 (69%) were males. The mean age of all patients was 56.3±10.84 years. Tp53 gene mutation in patients with chronic lymphocytic leukaemia was found only in 19(13.7%) patients. Among these patients 15(10.9%) were male and 04(2.9%) were females. Age and gender were not statistically significant with Tp53 mutation with a p-Value > 0.05 at a 95% confidence interval. Conclusion: In a cohort of Pakistani patients with Chronic lymphocytic leukaemia, TP53 gene mutation was found in 19(13.7%). Keywords: Chronic lymphocytic leukaemia; CLL; Tumour suppressor gene; TP53; Fluorescence in Situ hybridization; FISH